Penurunan Amonia pada Air Limbah Domestik Menggunakan Moving Bed Biofilm Reactor (MBBR) dengan Penambahan Mikroalga Chlorella Sp. - Pamungkas, Lestari Ayu Septian; Rosariawari, Firra (Universitas Ibn Khaldun, 2024)
Domestic wastewater contributes 60% of water pollution, mainly due to households dumping their wastewater into drainage channels. Domestic wastewater contains organic and inorganic pollutants such as BOD, COD, TSS, and ammonia. Biological treatment can reduce the pollutant levels in domestic wastewater by using microalgae Chlorella sp. in suspension and attached to form biofilm on MBBR.. The research aims to examine and determine the effectiveness of MBBR with microalgae Chlorella sp. in domestic wastewater treatment. The research focuses on the role of microalgae biofilm in reducing ammonia concentration in domestic wastewater. The research uses MBBR with different volumes of kaldnes 3 media (10%, 20%, and 30%) and different retention times (8 hours, 24 hours, 60 hours, and 120 hours). The highest biofilm formation of microalgae Chlorella sp. occurred in reactor C7 (kaldnes 20%) with an initial cell density 10.630x104 cells/mL at a retention time of 60 hours (2.5 days). The reactors with microalgae Chlorella sp. had the best ammonia removal ability compared to the control reactors. The highest removal was in reactor C7 (kaldnes 20%) with 98.84% removal and 0.048 mg/L residual ammonia at a retention time of 60 hours (2.5 days). Microalgae Chlorella sp. can oxidize ammonia to nitrate through nitrification process involving Nitrosomonas and Nitrobacter bacteria.